Investigation of the Attitudes of Primary School Teachers Towards Refugee Students - Kara, Veysel; Başaran, Mehmet (My University, 2022)
This study aims to examine the attitudes of primary school teachers who have refugee students in their classes towards these students. The convergent parallel pattern, one of the mixed research designs, was used in the study. The study data were obtained from 311 primary school teachers, with 197 female and 114 males, working in Şahinbey and Şehitkamil districts of Gaziantep. In the study, \"Demographic Information Form,\" \"Refugee Student Attitude Scale\", and \"Semi-structured Interview Form\" were prepared by the researchers were used as the data collection tools. While the SPSS 23.0 program was used to analyze the quantitative data obtained with the data collection tools, descriptive analysis was employed in the analysis of the qualitative data. According to the statistical analysis results, it was found that the overall scale and proficiency sub-dimension of the scale differed significantly in favor of male teachers in terms of gender variable, proficiency sub-dimension in favor of 51-60 age group in terms of age variable, According to the number of refugee students in teachers' classrooms, in favor of teachers with one refugee student in the overall scale and in the sub-dimensions of adaptation and proficiency Proficiency dimension in favor of teachers who served 21+ years in terms of years of service. In the content analysis of the interviews, it was revealed that the teachers had a language problem with their communication with the refugee students, and they tried to overcome this problem through Turkish-Arabic-speaking students or translators, which was a language problem in the adaptation of the refugee students and those parents had a negative view of co-education, That teachers planned activities and group games to overcome the adaptation problem. In addition, considering that the language problem and reading comprehension are the biggest problems in refugee education, the teachers underlined that there should be no discrimination and that language education should be provided to the refugee students and their parents as the key recommendations. The findings were discussed in the light of the literature, and the recommendations were made for the practitioners and researchers.
Keywords: Attitude; inclusive education; refugee student